Syhthesis, Characterization and Antimicrobial Studies of Isatin Thiosemicarbazones Derivatives of Dichlorobis(cyclopentadienyl) hafnium(IV) (Asian Journal of Applied Sciences, 2015)
The reactions of Cp2HfCl2, with thiosemicarbazones (LH) derived from isatin and 4-nitrophenyl substituted (IPTSH) and 4-methyl phenyl substituted (IMTSH) thiosemicarbazide in various stoichiometric rations have been studied and the complexes of the type [Cp2HfCl(L)] and [Cp2Hf(L)3] are obtained. Tentative structural conclusions are drawn for the reaction products based upon elemental analyses, electrical conductance, magnetic moment and (UV-Vis, IR, 1H NMR and 13C NMR) spectral data. Gram positive, gram negative bacteria and unicellular, multicellular fungi have been used for the evaluation of antimicrobial activity with selected antibiotics for the comparison. 4-Nitro Phenyl substituted moiety exhibited promising antibacterial and antifungal activities.